2003
DOI: 10.14236/jhi.v11i4.567
|View full text |Cite
|
Sign up to set email alerts
|

The development and evaluation of a computerised decision support system for primary care based upon 'patient profile decision analysis'

Abstract: Objective To develop and evaluate in primary care a computerised decision support system for the management of stroke patients based upon 'patient profile decision analysis'. Design The decision support system incorporated the findings of 960 Markov models examining the decision to prescribe aspirin in the secondary prevention of stroke. The models reflected each combination of nine risk factors that determined a patient's profile. The evaluation comprised a qualitative interview and a questionnaire administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…We found that primary care clinicians perceive ease of use to be the most important feature for adoption of CDSS. These results concur with previous studies on adoption of technology in primary care, and is believed to be related to limited consultation time, workload, computer self-e cacy and patients' expectations in primary care [27,35]. Due to time constraints and workload pressure, general practitioners may avoid using CDSS due to risk of encountering irrelevant and overwhelming amount of information, as well as compromising on direct communication with patients [36,37].…”
Section: External Factorssupporting
confidence: 88%
“…We found that primary care clinicians perceive ease of use to be the most important feature for adoption of CDSS. These results concur with previous studies on adoption of technology in primary care, and is believed to be related to limited consultation time, workload, computer self-e cacy and patients' expectations in primary care [27,35]. Due to time constraints and workload pressure, general practitioners may avoid using CDSS due to risk of encountering irrelevant and overwhelming amount of information, as well as compromising on direct communication with patients [36,37].…”
Section: External Factorssupporting
confidence: 88%
“…Five of the 152 studies assessed the perceived difficulty of the GPs’ decisions [ 16 - 20 ]. One did not report the difficulty data [ 18 ], leaving four studies to be analysed.…”
Section: Resultsmentioning
confidence: 99%
“…Some examples include the 'Computerised Antithrombotic Risk Assessment Tool' (CARAT) , Asthma Crystal Byte (Neville et al, 2000), 'clinical decision support of hypertension management' (Montgomery et al, 2000), pharmacokinetic-based gentamicin prescribing (Hwang et al, 2004), and the 'decision support for primary care' tool (Short et al, 2003). For such tools to be effective and relevant, they need to enable comprehensive patient assessment, so that decision-making is patient-oriented; to this end, patient age should only be one of many factors involved in the assessment.…”
Section: Clinical Decision Support Toolsmentioning
confidence: 99%